Caregivers' Intention to Vaccinate Their Children Under 12 Years of Age Against COVID-19: A Cross-Sectional Multi-Center Study in Milan, Italy - Lecce, Maurizio; Milani, Gregorio Paolo; Agostoni, Carlo; D'Auria, Enza; Banderali, Giuseppe; Biganzoli, Giacomo; Castellazzi, Luca; Paramithiotti, Costanza; Salvatici, Elisabetta; Tommasi, Paola; Zuccotti, Gian Vincenzo; Marchisio, Paola; et al. (Frontiers in Pediatrics, 2022)
The impact of Coronavirus disease 2019 (COVID-19) on the pediatric population is increasingly recognized. A widespread vaccination in childhood would provide benefits for children and might help ending the pandemic by enhancing community protection. Following recent approval by the European Medicines Agency (EMA) of Comirnaty (Pfizer-BioNTech) for children aged 5-11 years, we aimed to investigate caregivers’ intention to vaccinate their children < 12 years of age against COVID-19. A structured questionnaire was administered to caregivers of children aged < 12 years visiting the Emergency Department or the outpatient clinics in three major hospitals of Milan, Italy, from 20 September to 17 October 2021. A total of 612 caregivers were invited to participate and 604 accepted (response rate > 98%). Three questionnaires were excluded due to compiling errors and 601 were included in the analysis. A total of 311 (51.7%) caregivers stated they would have their child vaccinated, 138 (23%) would refuse to vaccinate their child and 152 (25.3%) were unsure. The intention to vaccinate the child was higher in caregivers vaccinated against COVID-19, in those with a bachelor’s degree or higher level of education, and in those with friends/acquaintances who became ill or died due to COVID-19. This study shows that increasing efforts are necessary to provide evidence-based tailored information to caregivers and to promote vaccination in this pediatric age group.